PERAN SUPERVISI KEPALA SEKOLAH DALAM IMPLEMENTASI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Vivi Apriyani; Muhammad Ihsan Dacholfany; Garianto Garianto (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the role of principal supervision in the implementation of instructional media to enhance the quality of learning at SD Negeri 2 Metro Barat. The study focuses on the stages of planning, implementation, feedback provision, and follow-up conducted by the principal to support teachers in effectively integrating instructional media into the teaching and learning process. A descriptive qualitative approach was employed in this research. Data were collected through in-depth interviews, classroom observations, and document analysis. The collected data were analyzed through data reduction, data display, and conclusion drawing, with the assistance of NVivo software to enhance analytical rigor and strengthen the credibility of the findings. The results reveal that systematically conducted principal supervision contributes significantly to the improvement of teachers’ competencies in implementing instructional media. Furthermore, the use of instructional media that is aligned with learning objectives, subject content, and students’ characteristics promotes greater student engagement, fosters a conducive learning environment, and improves learning outcomes in both cognitive and affective domains. The novelty of this study lies in its comprehensive analysis of the interrelationship between each stage of principal supervision and the effectiveness of instructional media implementation as a strategic approach to improving learning quality in elementary education.